Análise da legibilidade dos BR_GAAP versus legibilidade das notas explicativas de empresas brasileiras abertas - Borges, Guilherme de Freitas (2020)
Recent research has shown the recurring difficulties in the disclosure process of accounting information. In order to collaborate for the improvement of communication between the financial statements preparers, regulators and users of accounting information, this study aimed to investigate the relationship between the readability of the accounting standard and the readability of the notes to the financial reporting disclosed by Brazilian public-held companies. The advocated thesis is that the degree of readability of technical pronouncements affects the process of understanding the accounting standards by the statement preparer, impacting the readability of the notes. The study was carried out based on the rules issued by the Accounting Pronouncements Committee and the standardized financial statements published annually by the companies that make up the IBrX 50, in the period between 2010 and 2017. To measure readability, the Flesch Readability Formula was used. The characteristics of the research point to a descriptive study with a quantitative approach, in which multiple linear regression was used with panel data analysis. The results indicate a positive relationship between the readability of the standard and the readability of the notes to the financial statements. In addition, the variables related to the time of listing on the stock exchange and the issuance of ADR were statistically significant, contributing to the explanation of the model. Therefore, it was confirmed the thesis that accounting pronouncements with a greater degree of readability result in a best understanding the standard by the financial statements preparer, and, consequently, it implies more readable notes. This result can contribute to the performance of the agencies responsible for the accounting standards in the country and the process of convergence of international standards. Furthermore, it contributes to promoting the objective of the International Accounting Standards Board (IASB) to develop a unique set of high quality and understandable accounting standards.